2005
DOI: 10.1107/s010827010500911x
|View full text |Cite
|
Sign up to set email alerts
|

The α2-polymorph of salicylideneaniline

Abstract: N-Salicylideneaniline (SA), C13H11NO, belongs to the large family of aromatic Schiff bases. It is of particular importance owing to its reversible photoreactivity. SA forms two photochromic polymorphs, both with two non-coplanar benzene rings. In addition, we have recently discovered a planar polymorph, named the beta-polymorph, which will be discussed in a subsequent paper. We report here the structure of the alpha2-polymorph in the orthorhombic crystal system. This compound exhibits a strong intramolecular O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…The title compound ( Figure 1) is essentially co-planar with a dihedral angle of 9.28 (7)° between the aromatic rings. The bond distances and angles in the title compound are in accord with those reported for related salicylaldimine-based ligand systems (Karakaş et al, 2004;Arod et al, 2005;Cheng et al, 2005;Brink et al, 2009). …”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The title compound ( Figure 1) is essentially co-planar with a dihedral angle of 9.28 (7)° between the aromatic rings. The bond distances and angles in the title compound are in accord with those reported for related salicylaldimine-based ligand systems (Karakaş et al, 2004;Arod et al, 2005;Cheng et al, 2005;Brink et al, 2009). …”
Section: Methodssupporting
confidence: 81%
“…For related structures, see: Karakaş et al (2004); Arod et al (2005); Cheng et al (2005); Brink et al (2009). For related rhenium tricarbonyl complexes containing salicylaldimines, see: Brink et al (2011).…”
Section: Related Literaturementioning
confidence: 98%
“…Indeed, we observed that distances and angles of 1 are similar to those found in the nonplanar R 2 -polymorph. 15 The molecule is quite planar with a angle (Scheme 1) of 2.27(15)°, but ()6.93(27)°) is larger than ψ ()4.77(26)°). It appeared interesting to study (CrystalMaker) 33 other near-planar ( < 10°) SA derivatives found in the CCDC database.…”
Section: Resultsmentioning
confidence: 98%
“…1 and 2, respectively) [6]. The molecular conformation (E) of 1 is similar to that found in the crystal structure of the Schiff base Nphenylsalicylaldimine [7]. Fig.…”
mentioning
confidence: 61%